Digital Channel and Customer Satisfaction on Financial Services - Dian Primavera Widodo; Tantri Yanuar Rahmat Syah; Dimas Angga Negoro (Journal of Multidisciplinary Academic, 2020)
The purpose of this study aimed to examine how perceived justice moderates the relationship between the benefits offered by digital channels on financial services among cross-age study and the consequences of satisfaction with digital channels. This research employs a model in which digital channels offers comprehensive benefits, satisfaction and consequences that favour digital channels in addition, the model also tests the moderating role of perceived justice and product innovativeness in this context. In this study, we analysed many surveys among people who had applied for loans through digital channels and collected at various age and occupational backgrounds. Here, we obtain the survey correspondent with a total of 138 questionnaires. Results shows the offered of digital channels are positively related to customer satisfaction. In addition, the two consequences of customer satisfaction were analysed with two mechanism such as loyalty and positive word-of-mouth. Uncertainty avoidance, perceived justice and product innovativeness was not a significant moderator in this study.